2020
DOI: 10.1186/s12936-020-03489-x
|View full text |Cite
|
Sign up to set email alerts
|

The Gini coefficient as a useful measure of malaria inequality among populations

Abstract: Background Understanding inequality in infectious disease burden requires clear and unbiased indicators. The Gini coefficient, conventionally used as a macroeconomic descriptor of inequality, is potentially useful to quantify epidemiological heterogeneity. With a potential range from 0 (all populations equal) to 1 (populations having maximal differences), this coefficient is used here to show the extent and persistence of inequality of malaria infection burden at a wide variety of population le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…To calculate the Gini coefficient, we used the packages reldist [ 91 ] to calculate the Gini coefficient and boot [ 92 ] for bootstrapped error ranges [ 93 S1 Text ] to accommodate small sample sizes [ 41 ]. The confidence intervals are presented as the lower and upper boundaries of the Gini coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…To calculate the Gini coefficient, we used the packages reldist [ 91 ] to calculate the Gini coefficient and boot [ 92 ] for bootstrapped error ranges [ 93 S1 Text ] to accommodate small sample sizes [ 41 ]. The confidence intervals are presented as the lower and upper boundaries of the Gini coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, many states in southern areas of the country had substantially reduced prevalence in 2015 compared to 2010, but no further reduction was seen by 2018, which raises concerns on how to consolidate and continue to reduce malaria after some initial progress. It was previously shown that variation in prevalence among states in the 2015 survey was greater than the sub-national variation seen in comparable DHS surveys of infection in young children other highly endemic West African countries 23 , emphasising the need to understand divergent trends occurring within Nigeria.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, many states in southern areas of the country had substantially reduced prevalence in 2015 compared with 2010, but no further reduction was seen by 2018, which raises concerns on how to consolidate and continue to reduce malaria after some initial progress. It was previously shown that variation in prevalence among states in the 2015 survey was greater than the subnational variation seen in comparable DHS surveys of infection in young children in other highly endemic West African countries, 23 emphasising the need to understand divergent trends occurring within Nigeria.…”
Section: Discussionmentioning
confidence: 95%
“…For each of the six major geographical zones of the country, the overall Mantel-Haenszel-adjusted prevalence ratio (PR adj ) is plotted with a purple diamond symbol (with 95% CIs), showing significant overall declines: North-West PR adj =0. 23 emphasising the need to understand divergent trends occurring within Nigeria.…”
Section: Discussionmentioning
confidence: 99%